Treinamento por Simulação de Estudantes de Enfermagem e Medicina no Tratamento de Queimaduras: Revisão Integrativa. - Gomes, Darlene Moreira (2021)
Introduction: Burns are characterized as one of the most serious traumas affecting the population, evidencing a global public health problem. It is known that simulation training can be a valuable tool for better clinical practice, as it provides the student with the experience of an event close to reality, application of their knowledge in full and with the possibility of reviewing errors, in an environment safe and controlled, which creates greater security for the student and minimizes errors when this student attends a real patient in the internship field or in professional life. Objective: To analyze the evidence available in the literature on the use of simulation as a teaching method on burn treatment with nursing and medical students. Method: This is an integrative literature review. Research question: What is the scientific evidence available in the literature on the use of simulation training as a teaching strategy for undergraduate nursing and medical students about the treatment of people with burn injuries? The inclusion criteria for the pre-selection of studies were: articles in English, Portuguese and Spanish, without a time frame. Exclusion criteria were duplicate articles, reviews, letters to the editor, editorial, brief comments and those that, after reading in full, did not respond to the purpose of this review. An instrument for critical assessment of methodological quality was used.Results: This is an integrative literature review. Results: The search was performed in the electronic databases/databases PubMed, LILACS, Web of Science and Embase, without determining the time limit. Initially, 281 potentially eligible studies were identified, 36 of which were duplicated in the electronic reference manager EndNote Web and, later, 9 in the Rayyan QCR software. Three scientific articles were included in this review. Students reported satisfaction with the tools used in the simulation; training by simulation through images of clinical burn cases in a simulated scenario, allowed the identification of themes such as patient-centered, realism and learning and the use of scenario-based simulation provides a structured and flexible model in the approach of students to the case clinic of a person with burn injuries. Conclusion: Active teaching strategies, such as the practice of clinical simulation, are important in the care of trauma caused by burn injuries as it allows students to understand their role in caring for people affected by these injuries. The realistic simulation prepares future nursing and medical professionals for clinical practice and for the development of skills, knowledge and attitudes in a controlled and safe environment.